TAp63 and ΔNp63 (p40) in prostate adenocarcinomas: ΔNp63 associates with a basal-like cancer stem cell population but not with metastasis - Galoczova, Michaela; Nenutil, Rudolf; Pokorna, Zuzana; Vojtesek, Borivoj; Coates, Philip J (Virchows Archiv, 2021)
Like other malignancies, prostate tumors are thought to contain cancer stem-like cells (CSCs) that are responsible for growth, metastasis, and therapy resistance. ΔNp63 (also called p40) is a regulator of normal prostate stem/progenitor cell activities and a marker of normal basal epithelial cells. The levels of ΔNp63 are reduced in prostate adenocarcinomas, although there is also evidence that ΔNp63 is involved in CSC regulation and drives metastasis to the bone. We studied metastatic deposits of prostate cancers with isoform-specific ΔNp63 and TAp63 antibodies. We identified p63-positive cells in only 3 of 42 metastatic prostate tumors (7%), including 2/38 (5.3%) "usual-type" adenocarcinomas. ΔNp63 and TAp63 isoforms were present in the nuclei of a small subpopulation (< 1%) of tumor cells in these metastases. ΔNp63-positive cells showed a basal-like cell phenotype (cytokeratin 8- and androgen receptor-negative, high molecular weight cytokeratin- and cytokeratin 19-positive), distinct from the tumor bulk. TAp63-positive cells were similar but were sometimes cytokeratin 8-positive. A subset of ΔNp63-positive tumor cells were CD44-positive, a marker of "basal" CSCs but were not positive for the "epithelial" CSC marker ALDH1. TAp63 was not associated with either of these CSC markers. None of the tumors containing p63-positive cells showed evidence of bone metastasis, compared with 28% of the p63-negative tumors. These data show that both ΔNp63 and TAp63 are present in only a small proportion of prostate adenocarcinomas and do not associate with metastasis. The data suggest heterogeneity of CSCs in prostate cancer, similar to other cancer types.
Keywords: dospělí; Phenotype; transkripční faktory; Bone Neoplasms; Adult; nádorové supresorové proteiny; lidé; Transcription Factors; nádory kostí; studie případů a kontrol; nádory prostaty; Aged, 80 and over; Prostatic Neoplasms; retrospektivní studie; Adenocarcinoma; Male; Tumor Suppressor Proteins; nádorové biomarkery; Aged; Case-Control Studies; Neoplastic Stem Cells; adenokarcinom; Biomarkers, Tumor; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; fenotyp; Retrospective Studies; Middle Aged; nádorové kmenové buňky; Humans